PENGARUH STRATEGI BAURAN PEMASARAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN HOTEL NOVOTEL MAKASSAR GRAND SHAYLA CITY CENTRE. - Asdin Juniardi; Siti Haerani; Abdul Razak Munir (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2018)
This study aims to determine the effect of Marketing Mix toward Customer Satisfaction And Customer Loyalty Novotel Novotel Grand Shayla City Center. This research uses descriptive approach and verifikatif research. Descriptive research is a study that aims to obtain a description of the characteristics of variables (marketing mix strategy, loyalty and satisfaction). Verifikatif research is a type of research that aims to determine the relationship between variables through a hypothesis testing using path analysis method with the help of Smart PLS 3.0 applications.The results showed that partially marketing mix have positive and significant effect to customer satisfaction, marketing mix have positive and significant effect to customer loyalty, and satisfaction have positive and significant influence to customer loyalty. The influence indirectly indicates that customer satisfaction can mediate the influence of marketing mix to customer loyalty in a positive and significant.